Trust and self-trust in leadership identity constructions: A qualitative exploration of narrative ecology in the discursive aftermath of heroic discourse - Maria Lundberg (Copenhagen Business School (CBS), 2019)
The phenomenology of trust and self-trust in narrative leadership identity constructions is a field less explored within leadership studies. With a critical lens, this study approaches the construction of leadership identity, offering a broadened perspective on post-heroic leadership identity constructions. The investigation builds on an empirical inquiry based on qualitative interviews with 20 leaders. The thesis examines aspects of the narrative ecology of trust and self-trust related to leadership identity constructions in a post-heroic leadership context. The investigation concentrates on how a dyadic coexistence of trust and self-trust in leadership language can be understood to operate as an underlying potency in leadership identity constructions. The discussion focuses on four main findings related to trust and self-trust in the leaders' stories. Based on an interpretative framework and building on a phenomenological and ethnomethodological perspective, I show how Ladkin's idea of the leadership moment, together with Lührmann and Eberl's identity theory as a model for leadership identity construction, correspond to the theory of narrative ecology, wherein the leaders operate as creative bricoleurs constructing their narrative identities by drawing upon resources in a narrative ecosystem. The discussion attempts to elucidate how trust and self-trust provide agency for post-heroic leadership mastery, replacing leadership agency associated with formal power and authority that links to traditional leadership ideas. As part of this, the text examines how the heroic and postheroic leadership paradigms operate as competing big "D" Discourses, occurring side by side in the little "d" discursive leadership-as-talk identity context. My main argument is that the tensionfilled contradiction between heroic and post-heroic leadership Discourse is resolved by metaphors fuelled by notions of trust and self-trust in discursive leadership practices, which function as narrative rescue remedies, providing the leader with identity resources that validate and stabilise the identity construct. In addition, a potential eclipse in the literature on trust in leadership research is examined, wherein I point to the absence of risk in the empirical material of this project, and ask how this nonappearance can be understood in a post-heroic leadership-identity context. Lastly, I look to how the leadership identity construction project materialised in this study can be understood in the light of a self-realisation, anti-establishment fashion in popular management.
hdl:10398/9736
Keywords: 650; Führungspersönlichkeit; Vertrauen; Persönlichkeitspsychologie; Norwegen